International Conference on Transportation and Development 2019 : selected papers from the international conference on transportation and development 2019, June 9-12, 2019, Alexandria, Virginia - Noyce, David A. 1961- (American Society of Civil Engineers, 2019)
Selected papers from the International Conference on Transportation and Development 2019, held in Alexandria, Virginia, June 9-12, 2019. Sponsored by the Transportation & Development Institute of ASCE. The collection contains 44 peer-reviewed papers on smart, safe mobility and cities. Topics include: data analytics in intersection operations and safety; connected vehicle safety; crash prediction and assessment; human factors in smart mobility analysis; driving simulation and modeling traffic flow in smart mobility analysis; construction engineering in smart cities; and smart applications in rail infrastructure. This proceedings will be of interest to practitioners, planners, researchers, and policymakers in a broad area of smart transportation and development.
Sponsored by the Transportation & Development Institute of ASCE.
Keywords: Traffic engineering -- Congresses.; Traffic monitoring -- Congresses.; Traffic flow -- Congresses.; Traffic congestion -- Prevention -- Congresses.; Intelligent transportation systems -- Congresses.; Smart cities -- Congresses.; Sustainable urban development -- Congresses.; elektronické knihy; electronic books